Increasing Technopreneurs for a Developing a Nation: The Majlis Amanah Rakyat (MARA) Experience - Suradi, Salpiah; M.Yasin, Ruhizan; Rasul, & Muhamad Sattar (Journal of Technical Education and Training, 2017)
Prevalence of advanced technology necessitates a change in the way people do businesses where technology.  Techno-entrepreneurs are those who have technopreneurship skills where they operate businesses by optimising the use of technology to innovate new products and services. Technopreneurship is a process of merging technology prowess with entrepreneurial talent and skills. Thus, developing technopreneurship skills (to increase technopreneurs) is becoming an important goal of TVET in Malaysia.  Majlis Amanah Rakyat (MARA), being a statutory agency and the largest in the Ministry of Rural and Regional Development, plays a dual role in education and entrepreneurship development.   In line with its tagline â€œEntrepreneurship and Global Educationâ€, MARA has been successfully implementing its education transformation in TVET in line with the countryâ€™s economic direction.  MARA synergizes entrepreneurship and vocational training with the aim to create â€˜glocalâ€™ technopreneurs.    The aim of this study was to identify the factors that contribute to the success of MARA in transforming into an effective agency in providing Technopreneurship Development initiatives and programs. Literature study was the main method used to gather information.  The findings indicate that the success of the agency in increasing the number of technopreneurs was made possible through a well formulated and implemented strategic plan. Among the strateges adapted is the establishment of  an Incubator, MARA Technopreneur Program, Tech-Entrepreneur Program (PUTEK),  Innovation and Research Unit (UNI), International Relation Unit, and MARA Cooperation Alumni graduate TVE institutions  (KALAM). Through their implementations, MARA has supported Malaysian demand for technopreneurs.